Análise espaço-temporal dos óbitos de covid-19 na cidade de Ituiutaba-MG (2020 a 2022) - Viali, Flávia Catarina Alves (2024)
This study conducts a space-time analysis of deaths due to COVID-19 in the city of Ituiutaba-MG from 2020 to 2022. The aim is to understand how the pandemic affected the local population, identifying mortality patterns in different demographic segments. The research includes the description of COVID-19 death cases, their relationship with demographic factors such as age, gender, and comorbidities, and the investigation of determinants for mortality patterns in different neighborhoods of the city. The hypothesis considered is that the higher number of deaths would follow national and Minas Gerais patterns, with a higher incidence among elderly individuals and those with comorbidities. The analysis of the geographical distribution of deaths seeks to understand its relationship with access to health services, population density, and socio-economic characteristics of neighborhoods. The methodology used data from the Epidemiological Surveillance of the Municipal Health Department of Ituiutaba/MG and techniques of descriptive, bibliographic, and documentary research. The results were presented through graphs, tables, and thematic maps, demonstrating the spatialization of deaths in the urban area of Ituiutaba. The mitigation and intervention strategies adopted by the city, such as social distancing, widespread testing, public awareness, vaccination, and cooperation between government spheres, were essential to reduce the impact of the pandemic. Ituiutaba's experience with COVID-19 reflects the global challenges faced during the pandemic, emphasizing the importance of effectively implementing public health measures and collaboration across different sectors to address public health crises.